Proteomic analysis of Arabidopsis thaliana (L.) Heynh responses to a generalist sucking pest (Myzus persicae Sulzer). (24th July 2015) - Truong, D.‐H.; Bauwens, J.; Delaplace, P.; Mazzucchelli, G.; Lognay, G.; Francis, F.; Leiss, K.
Abstract Herbivorous insects can cause severe cellular changes to plant foliage following infestations, depending on feeding behaviour. Here, a proteomic study was conducted to investigate the influence of green peach aphid (Myzus persicae Sulzer) as a polyphagous pest on the defence response of Arabidopsis thaliana (L.) Heynh after aphid colony establishment on the host plant (3 days). Analysis of about 574 protein spots on 2‐DE gels revealed 31 differentially expressed protein spots. Twenty out of these 31 differential proteins were selected for analysis by mass spectrometry. In 12 of the 20 analysed spots, we identified seven and nine proteins using MALDI‐TOF‐MS and LC‐ESI‐MS/MS, respectively. Of the analysed spots, 25% contain two proteins. Different metabolic pathways were modulated in Arabidopsis leaves according to aphid feeding: most corresponded to carbohydrate, amino acid and energy metabolism, photosynthesis, defence response and translation. This paper has established a survey of early alterations induced in the proteome of Arabidopsis by M. persicae aphids. It provides valuable insights into the complex responses of plants to biological stress, particularly for herbivorous insects with sucking feeding behaviour.